PROFESIONALISME KEPALA LINGKUNGAN DI KECAMATAN LEMBEH SELATAN KOTA BITUNG - PARERA, SAMUEL (JURNAL ADMINISTRASI PUBLIK, 2017)
ABSTRACTThe head of the environment as an extension of the hand of the Government in the area of the smallestof the Wards have a strategic role in order to provide service to the community while bridgingthe implementation of Government programs and activities, therefore in carrying out the duties andfunctions of the head of the environment required for professionals. Professionalism is measured from theability to perform the duties and functions of a high quality, the right time, and with the procedures that are easyto understand. Of the approach, the concept of professionalism can be seen fromthe indicator: creativity (creativity), innovation (innovation) and Responsiveness (responsivity).This research was compiled based on qualitative research methods with data collection techniques in the formof observation, interview, documentation and technical analysis data used in this study is the analysisof qualitative data with the informant that add up to 48 people. The results showed that most headsof Environment in Lembeh South yet professional in carrying out the tasks and functions seenfrom less creative head of environment in providing services, as well as lack of innovation or new work beingdone in utilizing the technology. The factors that affect it, such as the level of education is still low,leadership, understanding of the tasks and functions, compensation, and yet the existenceof measurable performance evaluation. Therefore need to be laid out an activity of coaching and trainingfor the head of the environment in order to better understand the tasks and functions as well asincreasing competence.Keywords: Professionalism, Head Of Environment